Hubungan Antara Tingkat Stres dengan Motivasi Penyusunan Skripsi Pada Mahasiswa - Anggita Kinasih Lestari; Maria Margaretha Sri Hastuti (Journal of Counseling and Humanistic Studies, 2025)
This study aims to determine (1) how high the stress level of students writing a thesis is (2) how high the motivation level of students writing a thesis is (3) the relationship between stress levels and the motivation of students writing a thesis. This study is a correlational study. The sample consisted of 65 Guidance and Counseling Study Program students, Class of 2019 who were writing their thesis. The analysis technique used categorization, normality test, linearity test, and correlational hypothesis test. Data collection used the Stress Level Scale (44 valid items with a reliability test correlation value of 0.945) and the Motivation Level Scale (44 items with a reliability test correlation value of 0.933). The results of the study showed that: 1) the stress of students writing theses was at a moderate level (43%), 2) the motivation of students writing theses was at a high level (49%), 3) there was a significant relationship between the level of stress and the motivation of students writing theses (r = -0.316, significance 0.010 0.05).